PENGARUH LAPORAN KEUANGAN TERHADAP HARGA SAHAM (STUDI LITERATUR REVIEW) - Novitasari (Program Studi Perbankan Syariah, 2021)
This study aims to determine whether investors consider financial statement information in making decisions related to stocks. The research uses a literature review study method, where the researcher collects several journals related to the discussion in the research. (ROE), Debt Equity Ratio (DER), Current Ratio, not all studies show that financial statements are able to influence stock prices on the Stock Exchange. This is because there are a number of basic factors that can cause stock prices to rise or fall. In general, these factors are classified into internal factors and external factors. Internal factors are factors that arise from within the company. While external factors are factors that come from outside the company. This factor is arguably difficult to overcome. For example, there are problems related to macroeconomics. Of the two factors, external factors are more dominant in influencing stock prices.